Optimal methods for specifying information in the solution of integral equations with analytic kernels - Azizov, M.; Pereverzev, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We determine the exact order of the minimum radius of information in the logarithmic scale for Fredholm integral equations of the second kind with periodic analytic kernels and free terms. We show that the information complexity of the solution of Fredholm equations with analytic kernels is greater in order than the complexity of the approximation of analytic functions. This distinguishes the analytic case from the case of finite smoothness.